"Mbas Mi": Fighting COVID-19 Through Music in Senegal. (22nd March 2022) - Ndiaye, Bamba; Rowley, Margaret
Abstract: In the first two months of the COVID-19 pandemic, Senegalese musicians produced a large body of songs addressing the coronavirus. These songs engage with prophylaxes, symptoms, instructions in case of infection, and metaphysical conceptions about the origin and meaning of the pandemic. These songs are part of a national strategy aimed at containing and eradicating the coronavirus by developing "COVID-literacy": knowledge about the pandemic which is spread through music. In this article, we examine a socio-local history of music's use during health crises, its place in local religious communities, and how its use interlaces linguistic, traditional, and metaphysical tenets.